FAA541 : 2D character animation / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2018)
This course is an advanced course focuses on 2D animation which students immerse themselves in the theory and practice of animation in this intensive project-based hands-on workshop and seminar. Topics covered will include managing 2D digital animation projects, developing 2D cartoon character drawing, scripting for character animation, dope sheets, keyframing and inbetweening, line test. This course emphasizes the importance of the principles of cartoon character which able to convey movement, emotion and mood.